A seasonally dependent change in the distribution and physiological condition of Caiman crocodilus yacare in the Paraguay River Basin - Campbell, Hamish A.; Micheli, Mariana A.; Abe, Augusto Shinya [UNESP] (CSIRO Publishing, 2008)
The distribution and physiological condition of 116 Caiman crocodilus yacare was assessed over one year in the Southern Pantanal. Body mass and intermediary plasma metabolites were measured at three different time periods, representing large differences in the abundance of surface water. During the wet season the study site was completely submerged under water and C. c. yacare were distributed evenly throughout. High levels of [glucose] and [triglyceride] in the plasma indicated regular feeding. As the dry season progressed C. c. yacare became increasingly crowded around the remaining ponds. They showed a reduction in plasma [glucose] and [triglyceride], and an increase in plasma [beta-hydroxy-butyrate], signifying that they were feeding less and utilising fat reserves. At this sampling period, similar to 40% of the male C. c. yacare that were > 10 years old inhabited dry grassland and did not have access to water. These animals were significantly lighter than males of a similar length that had immediate water access, and plasma [uric acid] indicated that they had not fed for a long time and were metabolising tissue proteins. Essentially, the adult male C. c. yacare that inhabited dry grassland were in a state of energy deficiency. This was so severe in some animals that recovery seemed unlikely. The study suggests that fluctuations in the abundance of surface ground water may influence the size and structure of the C. c. yacare population in the Pantanal.